2013
DOI: 10.3945/ajcn.112.041632
|View full text |Cite
|
Sign up to set email alerts
|

Price discounts significantly enhance fruit and vegetable purchases when combined with nutrition education: a randomized controlled supermarket trial

Abstract: Discounting F&Vs is a promising intervention strategy because it resulted in substantially higher F&V purchases, and no adverse effects were observed. Therefore, pricing strategies form an important focus for future interventions or policy. However, the long-term effects and the ultimate health outcomes require further investigation. This trial was registered at the ISRCTN Trial Register as number ISRCTN56596945 and at the Dutch Trial Register (http://www.trialregister.nl/trialreg/index.asp) as number NL22568.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
188
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(198 citation statements)
references
References 50 publications
7
188
2
1
Order By: Relevance
“…This finding is echoed in findings that dietary variety is significantly associated with caloric availability from staples, but more strongly associated with caloric availability from non-staples (Hoddinott and Yohannes 2002). Furthermore, interventions that have deflated fruit and vegetable prices generally have found that consumption increases (Powell et al 2009;Waterlander et al 2013;Eyles et al 2012;French 2003;An et al 2013). …”
Section: Affordabilitymentioning
confidence: 99%
“…This finding is echoed in findings that dietary variety is significantly associated with caloric availability from staples, but more strongly associated with caloric availability from non-staples (Hoddinott and Yohannes 2002). Furthermore, interventions that have deflated fruit and vegetable prices generally have found that consumption increases (Powell et al 2009;Waterlander et al 2013;Eyles et al 2012;French 2003;An et al 2013). …”
Section: Affordabilitymentioning
confidence: 99%
“…The baseline period was two weeks and the intervention period lasted three weeks, which are standard time periods that have been shown to be sufficient for price intervention research (9,34,35) .…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, strong evidence for supermarket interventions, particularly those that provide nutrition education only at point of purchase, is somewhat lacking (8) , although interventions with a price intervention show more promise (13,45,46) . Nutrition education alone may not be adequate to drive real and sustained change to the household food supply.…”
Section: Discussionmentioning
confidence: 99%
“…BMI was categorised into three weight status groups consistent with the World Health Organization (20) cut-offs. Age was categorised into three groups consistent with those used in the latest Australian Health Survey (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) and 51-70 years).…”
Section: Methodsmentioning
confidence: 99%